Análisis de la relación del discurso como estrategia de personal branding que utilizan videobloggers colombianos en YouTube, y el consumo por parte de estudiantes de séptimo, octavo y noveno del Colegio Sagrado Corazón de Jesús, Hermanas Betlemitas de la ciudad de Palmira, en el año 2017-1 (2018)
This project was interested in describe and analyze the relationship between videobloggers’ speech as their personal branding within YouTube, and how these is relate to the consumption made by Sagrado Corazón de Jesus Bethlemitas Sisters’ 7th, 8th and 9th grade students, with these videobloggers on their videos and respective channels. Project’s aim is to watch the different variables in the students on the most subscribed colombian videobloggers; what are most watched videobloggers, who are the people they follow most, and also analyze their discursive content and identify elements on their style and image that persuade the analyzed students. In this project, we analyze the “YouTuber” phenomenon, an internet practice that consists in generating entertainment, educational or any type content to YouTube. Therefore, these users start generating content (mostly to teenagers) in this website, and they start applying new persuasion’s methods, to get new subscribers, views, and grow their fan base, which leads them to adopt a convincing speech based on themes of teens’ interest to gain everyday more and more. Finally, that’s the reason why this project was created, to analyze the transversal relationship that occurs in the network and that crosses several areas belonging to communication, such as immediacy and interactivity, and especially with discursive elements within the audiovisual narrative that videobloggers use to generate consumption in their videos and positioning of their own brands